Physiological and behavioural aspects of climate change vulnerability in ground-foraging passerines inhabiting South Africa’s Tankwa Karoo desert - McKechnie, Andrew E. (University of Pretoria, 2024)
Dissertation (MSc (Zoology))--University of Pretoria, 2024.